2021
DOI: 10.3389/fgene.2021.790426
|View full text |Cite
|
Sign up to set email alerts
|

Key Regulatory Differentially Expressed Genes in the Blood of Atrial Septal Defect Children Treated With Occlusion Devices

Abstract: Atrial septal defects (ASDs) are the most common types of cardiac septal defects in congenital heart defects. In addition to traditional therapy, interventional closure has become the main treatment method. However, the molecular events and mechanisms underlying the repair progress by occlusion device remain unknown. In this study, we aimed to characterize differentially expressed genes (DEGs) in the blood of patients treated with occlusion devices (metal or poly-L-lactic acid devices) using RNA-sequencing, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Remarkably, it has been shown that BTG1 could promote the deadenylation and/or degradation of mRNA to secure T cell quiescence [ 77 ], suggesting that BTG1 might be involved in a key mechanism underlying T cell quiescence. In addition, another APRO family member, Tob1, might be a key regulatory molecule in the process of endothelialization in the repair of atrial septal defects [ 78 ]. Tob1 might also play a fundamental role in keeping cells in a quiescent state, thereby obstructing the cellular proliferation of normal and/or cancer cells [ 79 ].…”
Section: Immune Pathway and Cardiac Arrhythmiasmentioning
confidence: 99%
“…Remarkably, it has been shown that BTG1 could promote the deadenylation and/or degradation of mRNA to secure T cell quiescence [ 77 ], suggesting that BTG1 might be involved in a key mechanism underlying T cell quiescence. In addition, another APRO family member, Tob1, might be a key regulatory molecule in the process of endothelialization in the repair of atrial septal defects [ 78 ]. Tob1 might also play a fundamental role in keeping cells in a quiescent state, thereby obstructing the cellular proliferation of normal and/or cancer cells [ 79 ].…”
Section: Immune Pathway and Cardiac Arrhythmiasmentioning
confidence: 99%